Monitoring membrane biofouling via ultrasonic time-domain reflectometry enhanced by silica dosing - Sim, S. T. V. (2013)
Detecting biofouling noninvasively in real-time has been a long-standing challenge in membrane processes. Ultrasonic Time Domain Reflectometry (UTDR) offers the potential to address this challenge when used in a ‘canary cell’ that samples a slip stream from the feed to the membrane process. However, adapting UTDR to detect biofouling is problematic owing to the small difference in acoustic properties between a biofouling layer and water or a membrane. In this study UTDR has been adapted to detect biofouling by periodic dosing of colloidal silica as an ‘acoustic enhancer’. This novel UTDR technique was applied to detect biofouling on flat sheet polyethersulfone ultrafiltration (UF) and thin film composite polyamide reverse osmosis (RO) membranes in a canary cell flow configuration. The UTDR response correlates with the transmembrane pressure and off-line measurements of the biofilm thickness via confocal laser scanning microscopy, the bacterial count, and extra-polymeric cellular substances (EPS). The acoustic enhancer was shown to have no effect on the viability of the bacteria. Hence, UTDR can be used for the noninvasive real-time detection of biofouling in high pressure membrane processes such as RO by periodic dosing of an enhancer such as colloidal silica in a canary cell.